Key Triggers of Osteoclast-Related Diseases and Available Strategies for Targeted Therapies: A Review - Bi, Haidi; Chen, Xing; Gao, Song; Yu, Xiaolong; Xiao, Jun; Zhang, Bin; Liu, Xuqiang; Dai, Min (Frontiers in Medicine, 2017)
Osteoclasts, the only cells with bone resorption functions in vivo, maintain the balance of bone metabolism by cooperating with osteoblasts, which are responsible for bone formation. Excessive activity of osteoclasts causes many diseases such as osteoporosis, periprosthetic osteolysis, bone tumors, and Paget’s disease. In contrast, osteopetrosis results from osteoclast deficiency. Available strategies for combating over-activated osteoclasts and the subsequently induced diseases can be categorized into three approaches: facilitating osteoclast apoptosis, inhibiting osteoclastogenesis, and impairing bone resorption. Bisphosphonates are representative molecules that function by triggering osteoclast apoptosis. New drugs, such as TNF and RANKL inhibitors (e.g., denosumab) have been developed for targeting the RANK/RANKL/OPG system or CSF-1/CSF1R axis, which play critical roles in osteoclast formation. Furthermore, vacuolar (H+)-ATPase inhibitors, cathepsin K inhibitors, and glucagon-like peptide 2 impair different stages of the bone resorption process. Recently, significant achievements have been made in this field. The aim of this review is to provide an updated summary of the current progress in research involving osteoclast-related diseases and of the development of targeted inhibitors of osteoclast formation.